Analisis Kesiapan Guru PAI dalam Pelaksanaan Kurikulum Merdeka Di SMP Negeri 1 Sangatta Utara - Auliyah, Diva Dhiyaul; Miramadhani, Avicni; Pandiangan, Anjani Putri Belawati (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
In the context of curriculum change, it is important for all stakeholders to understand and implement the established guidelines. This ensures that the objectives of the curriculum change can be achieved effectively and efficiently. One of the strategic steps taken is the preparation of clear and structured implementation guidelines. The purpose of the research in this journal is to analyze the readiness of pai teachers in implementing the independent curriculum in smp negeri 1 sangatta Utara. The research method used in this research is qualitative research method. the readiness of Islamic Religious Education (PAI) teachers at SMP Negeri 1 Sangatta Utara in implementing the Merdeka Curriculum shows positive developments. Although there are still some obstacles that need to be overcome, comprehensive measures have been taken to ensure the smoothness and effectiveness of learning. With continuous support and adaptation to the latest developments, it is hoped that the Merdeka Curriculum can provide maximum benefits for improving the quality of education in the school.